INFLUENCE HUMAN CAPITAL ON PERFORMANCE EMPLOYEES (A Study of Employees of PT. Pudak Scientific Bandung) - Lasvianti, Rekno Yuni (2016)
Background research is employee performance which annually decline, this is shown by frequently occurrence carelessness resulting in a broken, the target is not appropriate, are coming late for work, and absent without reason.These issues must be overcome that employee performance increase the company be achieved.An indication in improving the employee performance is with the human capital in company itself. The research method used is descriptive methods and verification with a population of 968 employees and respondents were 100 people.Analysis techniques used the correlation coefficient is pearson product moment and simple regression analysis.The testing of hypotheses use the t-test to identify the effects in partial. The results showed human capital and performance employees are in the high. The results of the correlation of 0,829, this means that the human capital with perfomance employees have a positive having a classification very strong. The results of simple regression analysis he obtained equation = 4,340 + 0,853x and KD = 0,687 or 68,7 % means variable influence human capital of the performance of 68,7 % employees, while the remaining fund of 31,3 % influenced by other factors or other variables that aren't pursuing writer. ---------- Latar belakang penelitian ini adalah kinerja karyawan yang setiap tahunnya mengalami penurunan, hal ini ditandai dengan sering terjadinya kecerobohan yang mengakibatkan alat rusak, pencapaian target tidak sesuai, terlambat masuk kerja, dan tidak masuk kerja tanpa alasan. Permasalahan ini harus segera diatasi agar kinerja karyawan optimal dan tujuan perusahaan tercapai. Indikasi dalam meningkatkan kinerja karyawan adalah dengan kualitas human capital dalam perusahaan itu sendiri. Jenis metode penelitian yang digunakan adalah metode deskriptif dan verifikatif dengan populasi 968 orang karyawan dan responden berjumlah 100 orang. Teknik analisis yang digunakan adalah koefisien korelasi pearson product moment dan analisis regresi sederhana. Pengujian hipotesis menggunakan uji t-test untuk melihat pengaruh secara parsial. Hasil penelitian menunjukan human capital dan kinerja karyawan berada pada kategori tinggi. Hasil perhitungan korelasi sebesar 0,829, artinya variabel human capital dengan kineja karyawan memiliki hubungan yang positif dengan klasifikasi sangat kuat. Hasil perhitungan analisisnregresi sederhana didapat persamaanY= 4,340 + 0,853X dan KD = 0,687 atau 68,7% artinya pengaruh variabel human capital terhadap kinerja karyawan sebesar 68,7%, sedangkan sisanya yaitu sebesar 31,3% dipengaruhi oleh faktor lain atau variabel lain yang tidak diteliti oleh penulis.